Teacher Readiness in Deep Learning for the IPAS Subject My Indonesia: Rich in Culture and History at SDN Sungai Lutut 4 Banjarmasin - Daud Yahya; Hijrah Safitri (Historia, 2026)
Deep Learning as a core approach in the Merdeka Curriculum requires teachers to design meaningful, contextual, and student-centered learning experiences. This study aims to describe the readiness level of teachers at SDN Sungai Lulut 4 Banjarmasin in implementing Deep Learning in the subject of Natural and Social Sciences (IPAS), particularly for the topic “My Indonesia Rich in Culture and History.â€ This research employed a descriptive qualitative approach through in-depth interviews, classroom observations, and document analysis of teaching materials. The main informants were two fourth-grade teachers at SDN Sungai Lulut 4 Banjarmasin. The findings indicate that teachers possess a basic understanding of the Deep Learning concept; however, they still encounter challenges in its implementation, particularly in planning authentic assessments, managing project-based activities, and utilizing local learning resources. In addition, teachers expressed enthusiasm for integrating Banjar cultural values, yet limited time and training hinder optimal implementation. In conclusion, the teachers’ readiness level is categorized as adequate, but further improvement in pedagogical competence, curriculum understanding, and school support is needed to ensure IPAS learning becomes deeper, more relevant, and contextual for students.